Banjar Traditional Architecture of the Tadah Alas Type in Cempaka, Banjarbaru, South Kalimantan - Selvianti, Khalida; Nisa, Khoirun; Hartati, Maulida; Aufa, Naimatul (RUSTIC, 2026)
Traditional Banjar architecture consists of eleven recognized house types, one of which is the Tadah Alas type. This study aims to identify and examine the architectural characteristics of a Tadah Alas traditional house located in Cempaka, Banjarbaru, South Kalimantan. Visually, the house exhibits differences from the commonly recognized Tadah Alas typology, prompting further investigation to verify its conformity. The research employs a comparative method by examining the architectural elements of the Cempaka house against established Tadah Alas characteristics as defined by cultural experts. Data were analyzed descriptively through narrative explanation and visual documentation, allowing for a systematic interpretation of observed features. The findings indicate that the house generally conforms to the Tadah Alas typology, with the exception of the panampik kecil space, which features a half-octagonal form. This configuration is unique and has not been identified in other known types of traditional Banjar houses, suggesting a local variation within the Tadah Alas typology.